Woman's eye, woman's hand : making art and architecture in modern India - Ruggles, D. Fairchild (New Delhi Zubaan, 2014)
Contributed articles.
Includes bibliographical references
Some illustrations on endpapers.
Keywords: Art, Indic; Art, Indic. -- 20th century; Architecture -- India -- History; Feminism -- India; Women in art; Women architects -- India